The persistence of stress-induced physical inactivity in rats: an investigation of central monoamine neurotransmitters and skeletal muscle oxidative stress - Buhr, Trevor J.; Reed, Carter H.; Wee, Olivia M.; Lee, Ji Heun; Yuan, Li-Lian; Fleshner, Monika; Valentine, Rudy J.; Clark, Peter J. (Frontiers in Behavioral Neuroscience, 2023)
Sedentary lifestyles have reached epidemic proportions world-wide. A growing body of literature suggests that exposures to adverse experiences (e.g. psychological traumas) are a significant risk factor for the development of physically inactive lifestyles. However, the biological mechanisms linking prior stress exposure and persistent deficits in physical activity engagement remains poorly understood. The purpose of this study was two-fold. First, to identify acute stress intensity thresholds that elicit long-term wheel running deficits in rats. To that end, young adult male rats were exposed to a single episode of 0, 50, or 100 uncontrollable tail shocks and then given free access to running wheels for nine weeks. Stress exposure resulted in a shock number-dependent 2-4 fold decrease in wheel running distance across the entire duration of the study. Second, to identify stress-induced changes to central monoamine neurotransmitters and peripheral muscle physiology that may be maladaptive to exercise output. For this study, rats were either exposed to a single episode of uncontrollable tail shocks (stress) or left undisturbed in home cages (unstressed). Eight days later, monoamine-related neurochemicals were quantified by ultra-High Performance Liquid Chromatography (uHPLC) across brain reward, motor, and emotion structures immediately following a bout of graded treadmill exercise controlled for duration and intensity. Additionally, protein markers of oxidative stress, inflammation, and metabolic activity were assessed in the gastrocnemius muscle by western blot. Results show that stress exposure curbed an exercise-induced increase of DA turnover measures in the prefrontal cortex and hippocampus, and augmented 5HT turnover in the hypothalamus and remaining cortical area. However, stress exposure also caused several monoaminergic changes independent of exercise that could underlie impaired motivation for physical activity, including a mild dopamine deficiency in the striatal area. Finally, stress potently increased HSP70 and lowered SOD2 protein concentrations in the gastrocnemius muscle, which may indicate prolonged oxidative stress. These data support some of the possible central and peripheral mechanisms by which exposure to adverse experiences may chronically impair physical activity engagement.